(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The density functional theory (DFT) is based on an exact correspondence between equilibrium one-particle densities and external potentials [10]. If we denote by n(r) the one-particle density of the system, the system can be characterized by an appropriate thermodynamic potential which attains its minimum [11] value for the correct (equilibrium) density n0(r). For the study of crystallization, the relevant thermodynamic potentials are the grand potential Ω and the intrinsic Helmholtz free energy F, the latter being a unique functional of the one–particle density.